Mythohistorical Interventions : The Chicano Movement and Its Legacies - Bebout, Lee (Book collections on Project MUSE., 2011)
"Mythohistorical Interventions" explores how myth and history impacted the social struggle of the Chicano movement and the postmovement years. Drawing on archival materials and political speeches as well as music and protest poetry, Lee Bebout scrutinizes the ideas that emerged from the effort to organize and legitimize the Chicano movement's aims.